Supply Considerations for Scaling Up Clean Cooking Fuels for Household Energy in Low‐ and Middle‐Income Countries. Issue 12 (3rd December 2019) - Puzzolo, E.; Zerriffi, H.; Carter, E.; Clemens, H.; Stokes, H.; Jagger, P.; Rosenthal, J.; Petach, H.
Abstract: Promoting access to clean household cooking energy is an important subject for policy making in low‐ and middle‐income countries, in light of urgent and global efforts to achieve universal energy access by 2030 (Sustainable Development Goal 7). In 2014, the World Health Organization issued "Guidelines for Indoor Air Quality: Household Fuel Combustion", which recommended a shift to cleaner fuels rather than promotion of technologies that more efficiently combust solid fuels. This study fills an important gap in the literature on transitions to household use of clean cooking energy by reviewing supply chain considerations for clean fuel options in low‐ and middle‐income countries. For the purpose of this study, we consider electricity, liquefied petroleum gas (LPG), alcohol fuels, biogas, and compressed biomass pellets burned in high performing gasifier stoves to be clean fuel options. Each of the clean fuels reviewed in this study, as well as the supply of electricity, presents both constraints and opportunities for enhanced production, supply, delivery, and long‐term sustainability and scalability in resource‐poor settings. These options are reviewed and discussed together with policy and regulatory considerations to help in making these fuel and energy choices available and affordable. Our hope is that researchers, government officials and policy makers, and development agencies and investors will be aided by our comparative analysis of these clean household energy choices. Key Points: Designing effective energy policies that support and accelerate transitions to clean cooking fuels is a top global priority Countries depend on a portfolio of fuels for cooking and should plan an optimal mix of clean fuels, both in the medium and long‐term Risk and sustainability of cookfuel supply chains depend on multiple factors that ultimately influence long‐term viability and scale